Flourish : a visionary new understanding of happiness and well-being - Seligman, Martin E. P. (Free Press, 2011)
Explains the four pillars of well-being--meaning and purpose, positive emotions, relationships, and accomplishment--placing emphasis on meaning and purpose as the most important for achieving a life of fulfillment.